Final Tax or Non-Final Tax: Strategies to Encourage Tax Compliance for Construction Service Companies as Potential Fiscal Support - Yohana Herdianly Br Nainggolan; Ayun Hanafiyah; Nafarida Santika Rahma (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
The construction sector is an important sector in producing building products. The construction services sector is able to contribute 10.44% to national GDP in 2021. However, this contribution is considered too minimal for the national GDP. Because many construction service companies admit losses. So that the government stipulates Alternative Minimum Tax (AMT) and PP No. 9 of 2022 regarding the final PPh rate, but it is not optimal. Therefore, the government needs to consider applying non-final PPh rates for construction services to overcome this problem. This study used descriptive qualitative and library research data collection techniques. The results of this research are expected to become the basis for changing final PPh to non-final in construction services and increasing tax compliance through bookkeeping as an expansion of the tax base.